Through the lens of photography, a silence: : urban views and public space in Natal (1902-1920) (TEL Tempo, Espaço e Linguagem, 2025)
This article aims to understand how photographic production in Natal enhanced urban transformations and conventionalized social codes in that space. The time frame refers to the taking of the first architectural photographs by Bruno Bougard, hired by the then governor Augusto Tavares de Lyra, until the consolidation of the professional photography profession in the 1920s. To this end, iconographic analyses were developed mediated by the airtable platform, in a way that was articulated with the problematization of the gaps in the investigation of visual historical testimonies.